Pelatihan Teknik Effective Public Speaking untuk Meningkatkan Kecakapan Berbicara Dalam Organisasi - Bunga Asriandhini (Artinara, 2023)
Effective Public Speaking Technique Training to Improve Speaking Proficiency in Organizations is held to provide solutions for problems within the IKBI organization PT. Nusantara Plantation Unit PG. Pangkah Afdeling Jatibarang as a partner. There were 27 participants who attended the training which was held at the IKBI PG meeting building in Pangkah subdistrict, Slawi Tegal, Central Java. The majority of its members are still constrained in communicating properly in conveying ideas, ideas, arguments both interpersonally and in public. The solution is that participants are first given an understanding by the facilitators in the form of sharing knowledge of Public Speaking techniques. Then the participants and the facilitators practice implementing these techniques, including techniques for preparing material, methods for delivering material, and vocal techniques. As the result, participants experienced an increase in speaking skills. This skill will increase with the experience as a speaker. Evaluation is carried out by comparing skills before the training and after the training takes place by giving questions and discussions. In addition, the facilitators records and assesses participants, understanding of the material and implementation.